Variations in length and growth of Greenland Halibut juveniles in relation to environmental conditions - Youcef, Wahiba Ait; Lambert, Yvan; Audet, Céline (Fisheries Research, 2015)
Greenland Halibut (Reinhardtius hippoglossoides), especially juveniles, are abundant in the St. Lawrence estuary, where oxygen levels are very low (18–25% saturation). Current data suggest that juveniles may be sedentary in this region. We investigated the relative importance of oxygen for juvenile growth in different areas occupied by juveniles in the estuary and Gulf of St. Lawrence (EGSL). More specifically, we examined the mean size-at-age for 1- and 2-year-old juveniles as well as the growth rate in different areas in relation to oxygen, depth, temperature, and juvenile density. Overall, oxygen concentration was found to affect juvenile Greenland Halibut growth: growth rate varied inversely with dissolved oxygen levels and significantly decreased when oxygen conditions were below 80 μmol/L (∼25% saturation). Temperature did not affect juvenile growth rates within the range found in these areas (4.95–5.14 °C). Mean lengths in 1- and 2-year-old juveniles (17 and 27 cm, respectively) as well as length increment estimates from 1 to 2 years old in the EGSL were much higher than those observed in other populations of Greenland Halibut. Length increment from ages 1 and 2 ranged between 8 and 12 cm for temperatures varying from 3.7 to 5.5 °C. We found the highest abundance of juveniles in bottom waters characterized by low oxygen concentrations and also found that there was continuous juvenile growth over the year; these observations suggest that the negative impacts of dissolved oxygen should be limited and/or largely compensated by other physical or biological characteristics of the EGSL, such as food abundance, food availability, and/or predator density. -- Keywords : Greenland Halibut Growth Hypoxia Temperature Fish density.